UPAYA ADMINISTRATIF SEBAGAI PERLINDUNGAN HUKUM BAGI RAKYAT DALAM SENGKETA TATA USAHA NEGARA - Hari Sugiharto; Bagus Oktafian Abrianto (Arena Hukum, 2018)
AbstractThis article try to analyze the concept of administrative effort and it implementation at the court. Enacted of Act Number 30 of 2014 on Government Administration leads the change of administrative court system in Indonesia. One of these change related to administrative effort. Legal issues in this article research is: first, do administrative effort must be taken before sues to administrative court; and second, whether original administrative decision or edministrative effort decision that used as an dispute object when apply a administrative lawsuit to administrative court. In accordance with the legal issues above, this article research is normative research to seek solutions to legal issues which are emerged. The results which have to be achieved are to provide the prescription of essential truth. There are several problems approach used in this study, such as statute approach and conceptual approach. Expected of this research can be found a norm that can be provides legal protection for the people especially in administrative dispute.Â In Addition, this research trying to analize of legal protection principle over government action on public law and law enforcement of legal public act by government that could be pursued if there is any detrimental to society.Â Abstrak Artikel ini bertujuan untuk menganalisa konsep mengenai upaya administratif dan penerapannya di pengadilan. Berlakunya Undang-Undang Nomor 30 Tahun 2014 tentang Administrasi Pemerintahan membawa perubahan dalam sistem peradilan tata usaha negara di Indonesia. Salah satu perubahan tersebut berkaitan dengan upaya administratif. Isu hukum dalam penelitian artikel ini pertama apakah upaya administratif harus ditempuh terlebih dahulu sebelum mengajukan gugatan sengketa tata usaha negara ke PTUN; dan kedua apakah keputusan tata usaha negara awal atau keputusan upaya administratif yang dijadikan obyek sengketa apabila mengajukan gugatan di Peradilan Tata Usaha Negara. Sesuai dengan isu hukum di atas, maka penulisan artikel ini menggunakan metode penelitian yuridis normatif untuk mencari pemecahan atas isu hukum yang timbul. Hasil yang hendak dicapai adalah memberikan preskripsi tentang kebenaran yang hakiki. Diharapkan dari penelitian ini didapatkan formulasi norma yang dapat memberikan perlindungan hukum bagi rakyat khususnya dalam hal sengketa tata usaha Negara dan menganalisis tentang hakikat dariÂ perbuatan hukum publik oleh pemerintah dan penegakan hukum terhadap perbuatan pemerintah dalam hukum publik yang merugikan masyarakat.